Integrated learning strategies for bullying prevention: a systematic literature review of approaches in physical and general education - Mashud; Fadillah, Muhammad; Ridha, Sahbana; Pebriyandi; Wulandari, Arina (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Bullying remains a critical issue affecting youth development in Indonesia, with a notable increase in reported cases between 2020 and 2023, particularly in junior high schools. Despite various large-scale interventions, bullying prevention embedded in the learning process itself—especially at the classroom level—has received limited attention. This study addresses the gap by exploring how learning-based strategies can serve as foundational solutions for broader bullying prevention efforts. Research Objectives: This systematic literature review aims to identify effective strategies for bullying prevention within both physical education (PE) and general education subjects, focusing on learning approaches that foster safe and inclusive classroom environments. Methods: A systematic review methodology was employed using the Publish or Perish application to extract data from CrossRef, Google Scholar, and Scopus. The PICO framework guided the research question, while the PRISMA flowchart structured the selection process. Finding/Results: From an initial pool of 2,799 articles, 10 met the inclusion criteria for qualitative synthesis. The analysis reveals that bullying prevention has been implemented through subject-integrated strategies in PE, civics, Islamic education, and social studies. Cooperative learning models have proven especially effective in PE, while general subjects have benefited from the integration of affective values (e.g., Islamic and Pancasila values) with cooperative approaches such as Numbered Heads Together (NHT), Student Teams–Achievement Division (STAD), and Jigsaw. Conclusion: The findings suggest that integrating cooperative learning with affective value education is a promising strategy for bullying prevention across subjects. Such approaches not only reduce bullying but also promote character education and social interaction. This review underscores the need for further research to expand these strategies and address bullying as a complex, global challenge.